EFFECTIVENESS OF USING RUNNING AND JUMPING EQUIPMENT IN PHYSICAL DEVELOPMENT OF GENERAL EDUCATION SCHOOL STUDENTS - A. A. Mamatkulov (Galaxy International Interdisciplinary Research Journal, 2023)
This article aims to improve the sports results of 13-14-year-old general school students by using effective methods and tools of teaching running and jumping techniques in physical development. Recommendations are given on improving the process of physical education classes and introducing innovative technologies based on science.